Advantages and disadvanteges [sic] of franchising to the franchisee in Nigeria - Oghifo, Ochuko Thompson (Universitetet i Nordland, 2012)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2012 The research pertain Nigeria Franchising system. It is a study that seeks to provide the necessary information of different stages of franchising system in Nigeria economy; example is like the different stages of product life circle. It is a descriptive case study which stands to investigate the advantages and disadvantages of Nigeria franchising system to the franchisees found in different industry sectors, using some models outlined by academics in the subject area of franchising in an international business perspective. With the adverse international business potentials and natural resources, Nigeria has what it take to attract business organization to invest in its economy. Though its political sectors has some floes, but it happens to be the most develop and biggest market with majority of natural resources in its rich Niger delta area in the sub-Saharan region of West Africa. It is a developing country that has the various potentials to improve the standard of living for its citizens through entrepreneurships and franchising being the gate way of entering into the global market. But it is really below standard that majority of the major world outlets of franchisors are still not in the country, it is for reason such like this that researchers has decided to investigate into the extent of franchising in Nigeria, which will also help to promote the industry in west Africa. Previous research on this sector has been focused on business format franchising, but this research will extend to cover all the parts of franchising in the field of academics and to bring into the awareness of the majority of people who happen to have no idea about the significant of franchising system and its contribution to societal benefit in a developing economy and the world at large.